Answer:
[tex](g\circ f)(-4) = 32[/tex]
Step-by-step explanation:
We are given the two functions:
[tex]f(x) = -2x - 3\text{ and } g(x) = 2x^2 - 2x - 8[/tex]
And we want to find the value of:
[tex](g\circ f)(-4)[/tex]
Recall that this is equivalent to:
[tex]\displaystyle = g(f(-4))[/tex]
Find f(-4):
[tex]\displaystyle \begin{aligned}f(-4) &= -2(-4) - 3 \\ &= 5 \end{aligned}[/tex]
Hence:
[tex]g(f(-4)) = g(5)[/tex]
Finally, find g(5):
[tex]\displaystyle \begin{aligned}g(5)& = 2(5)^2 - 2(5) - 8 \\ &= 32 \end{aligned}[/tex]
In conclusion:
[tex](g\circ f)(-4) = 32[/tex]